IMPLEMENTASI METODE TAKRIR UNTUK MEMPERCEPAT MENGHAFAL ALQUR’AN BAGI SISWA DI SEKOLAH DASAR - Arfandi Arfandi; Hasanah Hasanah; Zainuddin Zainuddin (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
In Indonesia, there are currently many places that provide education to thoroughly master the knowledge of the Al-Qur'an, but there are also places that provide education to become a Hafiz or Hafiza. SDIT Nurul Anshor is no exception, he is one of the educational institutions involved in the birth of little Hafiz and Hafiza. The takrir method is an effective method for improving memory and preserving the Al-Qur'an. To find out the effectiveness of memorizing the Koran with takrir strategies for students. In this study, the authors used a qualitative approach. There are two of his data in this survey: primary data and supplementary data. Data collection techniques include observations, interviews and documentation. Here are the findings: The implementation of Al-Qur'an memorization by takrir method in SDIT Nurul Anshor uses one page one page deposit system. Students then perform takrir before and after memorization in pairs, then a new memorization with ustadzah, and finally a memorization retest. Factors supporting the practice of Al-Qur'anic memorization in SDIT are parental and teacher motives, friend and environment motives, and good mood. Bad mood, unhealthy physical condition, laziness, and poor time management are the factors that prevent you from practicing Al-Qur'an memorization in SDIT.